A Serenata de Ciríaco de Cardoso e a sociedade portuense oitocentista (abordagem antropológica) - Heitor-Rigaud, João (Trabalhos de Antropologia e Etnologia, 2020)
The nineteenth century society of Oporto was clearly characterised by a taste for the arts, a cosmopolitan outlook and a hearty enjoyment of life, which explains the enthusiastic reception of Domingos Ciríaco de Cardoso’s Serenade, even though it was a lunda, a risqué dance of Angolan origin that had gained popularity with all social strata. In the twentieth century, with the accentuated decline of the city, the cultural brilliance and enormously rich heritage of the previous century was forgotten as it came to be erroneously regarded as a grim and sanctimonious time in which the drabness of life inhibited cultural development.